Analysis of Work Accident Risk in Production Section Using Hazard Analysis and Operability Study (HAZOP) and Analytical Hierarchy Process (AHP) (Case Study: PT XYZ) - Susanto, Gladis Permatasari; Sukmono, Yudi; Gunawan, Suwardi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
PT XYZ is a company that produces plywood. During the production process activities, there are potential risks that arise and can affect the safety and health of field workers. Therefore, this study aims to determine the risk analysis that occurs during the production process activities, determine the risk level and look for alternative improvement proposals on risks that have extreme levels. The method used to analyze the risk level in the production process is the HAZOP (Hazard Analysis And Operability Study) method and to determine the best improvement proposal using the AHP (Analytical Hierarchy Process) method. Based on the results of the analysis using the HAZOP method, there is a risk analysis of 35 risks with a total of 14 machine activities of which 57% for low risk with a total of 20 risks, 17% for moderate risk with a total of 6 risks, 17% for high risk with a total of 6 risks and 9% for extreme risk with a total of 3 risks. The proposed improvements were selected based on the weighting results using the AHP method. In the AHP method, criteria in the form of priority risks are used, namely the risk on the rotary machine (workers’ feet are injured when changing the rotary knife) with the highest weight of 0.665 with the selected alternative, namely the socialization of K3-related training and SOPs in changing knives in rotary machines with a weight of 0.512.